Evaluation of Intrarow Spacing on Growth and Yield Performance of Four Onion (Allium cepa L.) Varieties in Beyeda District, North Gondar, Ethiopia - Wubetie Adnew Wassie; Gashaw Fenta Assegahegn; Berhanu Abraha Tsegaye; Amare Bitew Mekonnen (Advances in Agriculture)
Onion (Allium cepa L.) is a vegetable crop that belongs to the genus Allium under the family Alliaceae produced widely throughout the world. Field experiments were undertaken to evaluate the different varieties and plant spacings on the growth and bulb yield performance of onion (Allium cepa L.) in Beyeda district, North Gondar, Ethiopia. Four different levels of spacing (6, 8, 10, and 12 cm) and four different types of varieties (Shallot, Nasik red, Robat, and Nafis) were arranged under randomized complete block design (RCBD) of factorial arrangement with three replications. The experiment was arranged in 4 × 4 factorial combinations, and the total area was divided into three blocks each of which comprised 16 treatment combinations and a total of 48 plots. The highest plant height (54.18 cm), leaf length (45.48 cm), and leaf diameter (1.47 cm) were recorded from the variety of Nasik red while the lowest plant height, leaf length, and leaf diameter were measured from shallot. The highest leaf number was observed from shallot (37.53) while the lowest leaf number was recorded from the Nafis variety. The longest bulb length (4.44 cm) and the widest bulb diameter (4.67 cm) were obtained from the Nafis variety while the shortest bulb length and narrowest bulb diameter were measured from shallot. Inversely, the highest bulb weight (54.50 g/plant), total biomass (94.75 g/plant), and unmarketable bulb yield (1.75 t/ha) were recorded from shallot while the lowest bulb weight, total biomass, and unmarketable bulb yield were recorded from the Robat variety. Intrarow spacing showed a significant effect on onion growth and bulb yield parameters, as the earliest (135 days) and the most delayed (146 days) maturity were recorded at 6 cm and at 12 cm spaces, respectively. The highest unmarketable bulb yield has been seen at 8 cm and the lowest at 12 cm space of the Nasik red variety. Similarly, the highest leaf number, leaf diameter, bulb diameter, bulb weight, total biomass, marketable, and total bulb yield were recorded at 12 cm space under the Nafis variety. Furthermore, under the shallot variety, the widest bulb diameter was recorded at 10 cm while the narrowest one was recorded at 6 cm space. Generally, based on the result of marketable bulb yield performance, Nafis variety at 12 cm and 8 cm spaces, Robat at 6 cm space, and Nafis red at 10 cm space, respectively, have effective performance for onion production. The interaction effects of intrarow spacing with different varieties did not have a significant effect on all of the growth parameters and yield components.